Mcp3 is a novel mitochondrial outer membrane protein that follows a unique IMP-dependent biogenesis pathway - Sinzel, Monika; Özbalcı, Çağakan; Brügger, Britta (EMBO reports, 2016)
Abstract Mitochondria are separated from the remainder of the eukaryotic cell by the mitochondrial outer membrane (MOM). The MOM plays an important role in different transport processes like lipid trafficking and protein import. In yeast, the ER?mitochondria encounter structure (ERMES) has a central, but poorly defined role in both activities. To understand the functions of the ERMES, we searched for suppressors of the deficiency of one of its components, Mdm10, and identified a novel mitochondrial protein that we named Mdm10 complementing protein 3 (Mcp3). Mcp3 partially rescues a variety of ERMES-related phenotypes. We further demonstrate that Mcp3 is an integral protein of the MOM that follows a unique import pathway. It is recognized initially by the import receptor Tom70 and then crosses the MOM via the translocase of the outer membrane. Mcp3 is next relayed to the TIM23 translocase at the inner membrane, gets processed by the inner membrane peptidase (IMP) and finally integrates into the MOM. Hence, Mcp3 follows a novel biogenesis route where a MOM protein is processed by a peptidase of the inner membrane.
Gesehen am 08.05.2020